Perfis de DNA de Salmonella spp. isoladas de produtos de frango e fezes de frango e humanas - Tejada, Talita Schneid (2013)
Salmonella is one of the main causative agents of foodborne diseases, and chicken-based products play a prominent role in this context, serving as vehicles to the microorganism. The present study aimed to provide data on the Salmonella spread in the poultry chain, check the occurrence of Salmonella and its different serotypes isolated from chicken stool, chicken products and human stool, as well as to verify the similarity between DNA profiles of Samonella isolated. Literature on the occurrence of Salmonella in the poultry chain was reviewed; parallel to it, a project in which 600 samples (200 chicken meat, 200 chicken stool and 200 human stool samples) were analyzed for Salmonella presence was developed. DNA profiles of isolated strains were obtained by PFGE and REP-PCR. The microorganism was isolated from 16 samples, 8 (8/200 4%) from chicken products, 4 of which (4/200 2%) from chicken stool and 4 (4/200 2%) from human stool. Salmonella serotype Schwarzengrund was found to prevail both in chicken meat and chicken stool, followed by serotype Mbandaka, whereas serotype Panama prevailed in humans. Strains with indistinguishable genotypes were found to be present both in chicken stool and chicken products, suggesting that the chicken contamination on the farm remained in the processed product. In humans, the isolated strains were indistinguishable between one another, suggesting an outbreak occurrence; however, the isolated serotypes in humans were not the same as those in chickens, which is probably related to different contamination sources.